Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1111/caim.12410
|View full text |Cite
|
Sign up to set email alerts
|

Prototypes as identity markers: The double‐edged role of prototypes in multidisciplinary innovation teams

Abstract: Prototypes play a powerful role in facilitating the work of multidisciplinary innovation teams, but if not properly managed, they may inhibit innovation processes. This paper inquires into the tensions that exist around the use of prototypes in multidisciplinary teams. We studied the relationship between work identities (related to teams and subgroups within teams) and prototypes with a field study of a multidisciplinary team in an emergency department, in charge of redesigning the layout of the unit. Results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 51 publications
(118 reference statements)
0
12
0
Order By: Relevance
“…It can also implement a subtle mix of different forms of coactive power, such as the combination of physical artefacts (e.g., prototypes) and discursive practices, to initiate a collective reframing of ideas and their coconstruction. Prototypes are already acknowledged as identity markers that facilitate communication across disciplines within a team (Bechky, 2003; Dosi et al, 2020). Therefore, our results extend this beneficial role to wider social interactions with external audiences.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It can also implement a subtle mix of different forms of coactive power, such as the combination of physical artefacts (e.g., prototypes) and discursive practices, to initiate a collective reframing of ideas and their coconstruction. Prototypes are already acknowledged as identity markers that facilitate communication across disciplines within a team (Bechky, 2003; Dosi et al, 2020). Therefore, our results extend this beneficial role to wider social interactions with external audiences.…”
Section: Discussionmentioning
confidence: 99%
“…To reduce intergroup distinctiveness and avoid misunderstandings, individuals should define new overarching identities based on distinct attributes (Bechky, 2003; Mattarelli & Tagliaventi, 2010). This is particularly true for multidisciplinary teams (such as creative teams) characterized by subgroups that define themselves with occupation‐derived values and beliefs, which must create a minimum level of commitment and coordination (Dosi et al, 2020) with one another and with audiences. Cross‐cutting identities where the values of two or more groups partially overlap can also be defined within organizations and at their boundaries with external audiences (Ashforth et al, 2008; Brewer & Pierce, 2005).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…An ultrasound scanner at the CH (Arcmed) was seen as representing the ability to offer advanced hospital services, and documentation (at Health) related to washing and dressing patients suggested that the CH was a place “like‐home, where we care.” Resources became boundary objects influenced by identity dynamics (e.g. Bechky, 2003; Dosi et al, 2020), around which the community discussed collective practices that endorsed the new organizational arrangement as identity workspace. Managers should assess equipment, documents, routines, and norms not only in terms of conventional criteria—their economic convenience, efficiency, usefulness, but also in terms of the opportunities they offer to the realization of individual aspirations and goals.…”
Section: Discussionmentioning
confidence: 99%
“…An ultrasound scanner at the CH (Arcmed) was seen as representing the ability to offer advanced hospital services, and documentation (at Health) related to washing and dressing patients suggested that the CH was a place "likehome, where we care." Resources became boundary objects influenced by identity dynamics (e.g Bechky, 2003;Dosi et al, 2020),. around which the community discussed collective practices that endorsed the new organizational arrangement as identity workspace.…”
mentioning
confidence: 99%